A Carleman Estimate on Groups of Heisenberg Type (Journal of Partial Differential Equations, 2020)
A Pohozaev-Rellich type identity for the p-sub-Laplacian on groups of Heisenberg type, G, is given. A Carleman estimate for the sub-Laplacian on G is established and, as a consequence, a unique continuation result is proved.
Keywords: Pohozaev-Rellich type identity; Carleman estimate; unique continuation; sub-Laplacian; group of Heisenberg type